2009
DOI: 10.1088/0952-4746/29/3/004
|View full text |Cite
|
Sign up to set email alerts
|

Patient and staff doses for some complex x-ray examinations

Abstract: The aim of this study was to measure patient and staff doses simultaneously for some complex x-ray examinations. Measurements of dose-area product (DAP) and entrance skin dose (ESD) were carried out in a sample of 107 adult patients who underwent different x-ray examinations such as double contrast barium enema (DCBE), single contrast barium enema (SCBE), barium swallow, endoscopic retrograde cholangiopancreatography (ERCP) and percutaneous transhepatic cholangiography (PTC), and various orthopaedic surgical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…In our multiple linear regression model we found that the conduct of therapy, especially the placement of biliary stent, implied a higher DAP. This has already been reported in many previous studies (2)(3)(4)8) showing that therapeutic ERCP could be six times higher. In fact, in most studies regarding radiation dose, authors differentiate between diagnosis and therapeutic ERCP, treating them as two different techniques.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our multiple linear regression model we found that the conduct of therapy, especially the placement of biliary stent, implied a higher DAP. This has already been reported in many previous studies (2)(3)(4)8) showing that therapeutic ERCP could be six times higher. In fact, in most studies regarding radiation dose, authors differentiate between diagnosis and therapeutic ERCP, treating them as two different techniques.…”
Section: Discussionsupporting
confidence: 79%
“…In this sense, the most described is therapeutic indication that could increase the dose area product (DAP) three to four times (2,3). Therapeutic options are becoming more com-…”
Section: Introductionmentioning
confidence: 99%
“…Few studies that evaluate radiation exposure to staff during ERCP are found in the recent literature [11,[19][20][21][22][23]. These studies confirm that the radiation exposure to personnel undertaking ERCP is not negligible and radiation protection measures should be taken.…”
Section: Discussionmentioning
confidence: 75%
“…Such studies have either been on various interventional radiology procedures including ERCP [9,11,16,21], relatively old studies focusing on protective measures [13,32], or phantom studies [18,22]. Such studies were undertaken at different periods and with different fluoroscopy devices (fixed X-ray source situated either under or above the patient bed vs. C-arm devices).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years, only a handful of studies have tackled the issue of radiation exposure in staff performing ERCP [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] in which ERCP was either evaluated as a part of several interventional radiological procedures or as a simulation study [9,11,16,18,21,22]. However, the year of publication, fluoroscopy equipment used, protective methods used against radiation exposure, and the body parts that were tested for exposure showed significant variations between studies.…”
Section: Introductionmentioning
confidence: 99%